Stressful life events during pregnancy and offspring depression: evidence from a prospective cohort study - Kingsbury, Mila; Weeks, Murray; MacKinnon, Nathalie; Evans, Jonathan; Mahedy, Liam; Colman, Ian (Université d'Ottawa | University of Ottawa, 2016)
OBJECTIVE: The fetal programming hypothesis posits that in utero exposure to stress can alter prenatal brain development and lifelong stress response. However, human studies linking objective prenatal stressors to offspring mental illness, especially depression, are rare. The purpose of this study was to examine the association between mothers' exposure to prenatal stressful life events (SLEs) and offspring depression. METHOD: The sample comprised 10,569 members of a prospective population-based cohort, the Avon Longitudinal Study of Parents and Children (ALSPAC). Mothers reported on the occurrence and impact of 42 prenatal SLEs. Offspring depressive symptoms were assessed using a computerized version of the Clinical Interview Schedule-Revised (CIS-R) at age 17 to 18, as well as 13 self-report statements from the Short Mood and Feelings Questionnaire (SMFQ) at 6 time points from ages 10 to 11 to 18 to 19. Latent class growth analysis (LCGA) was used to identify trajectories of depressive symptoms across adolescence. RESULTS: After adjusting for potential confounders, a 1-unit increase in maternal SLE scores (range, 0-168) during gestation was associated with increased offspring depressive symptoms (β = 0.07, p < .01) and major depression (odds ratio [OR] = 1.03, 95% CI 1.01, 1.06) at age 17 to 18. LCGA revealed 4 trajectories of depressive symptoms. High maternal SLEs (fourth quartile) were associated with membership in the trajectory characterized by stable, high levels of depression from age 10 to 11 to 18 to 19 years (OR = 1.72, 95% CI = 1.09, 2.71). CONCLUSION: These results provide support for the fetal programming hypothesis, demonstrating that prenatal exposure to acute stress is associated with offspring depression in adolescence. Stress management may be of benefit for expectant mothers.
Keywords: Depression; Prenatal; Stress; Epidemiology